Retrospective clinical study on the efficacy and complications of interventional embolization in the treatment of scalp arteriovenous fistula - Han, Wenliang; Yang, Kexin; Gao, Wei; Wu, Xuejun; Huo, Ran; Xu, Lei (Frontiers in Neurology, 2024)
IntroductionScalp arteriovenous fistula (AVF) is a rare and intricate vascular anomaly characterized by a direct connection between an artery and a vein, without an intervening capillary system. This anomaly can induce significant local hemodynamic changes and is associated with various complications, such as pain, a pulsatile mass, increasing swelling, and venous hypertension skin ulcerations which may be non-healing. This study aimed to evaluate the efficacy and safety of interventional embolization treatments for scalp AVF at Shandong Provincial Hospital.MethodsThis retrospective clinical analysis assessed 21 patients who underwent interventional embolization between 2018 and 2024. Patients included were those treated in the vascular surgery department at Shandong Provincial Hospital, who had comprehensive medical records and follow-up data. Treatment methods, outcomes, and complications were thoroughly analyzed through patient medical records.ResultsAmong the patients studied, direct puncture was the most prevalent treatment method, employed in 42.86% (9/21) of cases, followed by various combinations of arterial, venous, and direct approaches. Ethanol, used in 85.71% (18/21) of the cases, demonstrated its broad efficacy and application in clinical settings. Immediate imaging post-treatment confirmed a cure rate of 85.71% (18/21). The main postoperative complications included swelling, with some patients also experiencing nodules, scabbing, or hair loss.ConclusionInterventional embolization has proven to be a safe and effective method for managing scalp AVF, significantly minimizing complications. Future research should focus on further optimizing these treatment methods to enhance efficacy and improve patient quality of life.